A study to investigate the relationship between emotional intelligence and life satisfaction / Syarifah Nuratikah Fatihah Syed Sahaimi - Syed Sahaimi, Syarifah Nuratikah Fatihah (Faculty of Business and Management, 2019)
Life satisfaction is the symbolizing an overall criterion or an ultimate result experience of human. It is an overall assessment of attitudes and feelings about human's life at a particular point in time which ranging from negative to positive. Life satisfaction is characterized, which is aligned to the cognitive theory, as "person's cognitive judgment about comparisons according to the compatibility of their own life conditions with the standards". The aim of this this study is to examine and reviews the predictive relationship between emotional intelligence toward life satisfaction in a group of worker at Yayasan Terengganu. Moreover, it is to examine whether the three factors of emotional intelligence which social support, self-esteem and perceived stress own the relationship towards life satisfaction. The respondent were participated in this study was 150 out of 250 of the respondents at Yayasan Terengganu. In order to collect the data, the questionnaires were used in this study. The questionnaire consists of the demographic background, factor emotional intelligence and life satisfaction. This chapter will show all the result from data analysis and data interpretation by using software which is Statistical Package for Social Science (SPSS) version 22.0. This software are used in this chapter to produces all the result that researchers want to conduct by having an exact result for the research at Yayasan Terengganu Company. While, it also enables the researchers to carry out various analysis and that can be used to obtain the answers from the research questions and research objectives. The result indicates that there is a significant relationship between the three